Identifikasi Boraks pada Makanan dengan Ekstraks Oxalis Triangularis untuk Meningkatkan Aktivitas Belajar Peserta Didik di MTs Negeri 4 Kulon Progo - Siti Suwarni (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This paper is prepared as a means of publishing creative, innovative, and efficient work that can help teachers and students in learning, especially science subjects, especially in borax testing on food by utilizing ingredients that are easy to make and easy to get in the environment around the school. This paper presents how to create and use borax indicators from butterfly plant extract (Oxalis triangularis) performed based on knowledge, existing literature, and experiments. This research uses qualitative research methods with a literature review approach. The subject of the study was students of class VIII-C MTs Negeri 4 Kulon Progo in the Odd Semester of the 2022/2023 Academic Year. Based on the data obtained, it can be concluded that butterfly plant extract (Oxalis triangularis) can be used for the identification of borax in food. The use of butterfly plants (Oxalis triangularis) for the identification of borax in food can increase student learning activities and can shape the character of students to be sensitive to the environment and utilize the environment as a learning medium, especially in science subjects in food test materials.